Dukungan Sosial, Interaksi Keluarga, dan Kualitas Perkawinan pada Keluarga Suami Istri Bekerja - Tin Herawati; Berti Kumalasari Zubairi; Musthofa Musthofa; Fatma Putri Sekaring Tyas (Jurnal Ilmu Keluarga dan Konsumen, 2018)
The phenomenon of dual-earner family can lead to changes in social support and family interaction that affect the quality of marriage. This study aims to analyze the influence of social support and family interaction on the quality of marriage in families with husband and wife work. Respondent in this research is the wife who works as the civil servant (PNS) in Bogor City Government and have school age child (6-12 year) and willing to be respondent, with an amount of 60 working wives. Respondents were chosen purposively. The results show that more than half of wives receive high social support from extended families and neighbors. Wives get optimal emotional support from extended family. Family interactions that include husband-wife and mother-child interactions show that almost all families have good interactions. The highest proportion is that two-thirds of wives feel that mother-child interaction is in the high category whereas the most substantial portion of wives assessing husband-wife interaction is in the moderate category. Meanwhile, the quality of marriage seen from the dimensions of happiness and satisfaction shows that the highest proportion of wives feels the quality of marriage is high. This study found that the factors that have the most positive significant effect on marital quality in a family with husband and wife work are family interaction.